“Teacher Burnout Is One of My Greatest Fears”: Interrupting a Narrative on Fire - Williams, Emily P.; Tingle, Elizabeth; Morhun, Janelle; Vos, Sally; Murray, Kerri; Gereluk, Dianne; Russell-Mayhew, Shelly (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
Teacher burnout is often positioned as a common result of the complex demands of the teaching profession (García-Carmona et al., 2019). While there is no denying the demanding nature of teaching, in this article we present an alternative perspective on the widespread burnout discussion that distinguishes between burnout and the complexities of teacher attrition, and offer a more hopeful and strengths-based approach to the teaching profession. In a qualitative study that analyzed the anticipatory beliefs that pre-service teachers expressed in a reflective assignment for a course focused on Comprehensive School Health (CSH), we found evidence to suggest that the burnout narrative may threaten teacher candidates’ self-efficacy before entering the teaching profession. We call for a disruption to the overemphasis of burnout narratives in teacher education programs as they may undermine the profession.